2012
DOI: 10.7224/1537-2073-14.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Depression Levels and Interferon Treatment in People with Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is the most common cause of neurologic disease in young and middle-aged adults, and 75% of patients are female. Nearly one in two patients with MS will experience clinically significant depression-approximately three times the prevalence rate in the general population. This study used a cross-sectional approach to examine the link between depression levels and use of interferon medications among individuals with MS. Data were collected from 694 patients of the Multiple Sclerosis Compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Metz et al ( 25 ) report a more beneficial effect of glatirameracetat than β interferon on fatigue after 6 months of treatment. Other studies found no relationship between depression and treatment with interferons ( 26 , 27 ). One study reported decreased quality of life, worsened fatigue, and depression under treatment with β interferon ( 28 ).…”
Section: Introductionmentioning
confidence: 82%
“…Metz et al ( 25 ) report a more beneficial effect of glatirameracetat than β interferon on fatigue after 6 months of treatment. Other studies found no relationship between depression and treatment with interferons ( 26 , 27 ). One study reported decreased quality of life, worsened fatigue, and depression under treatment with β interferon ( 28 ).…”
Section: Introductionmentioning
confidence: 82%
“…This is important considering that the prevalence of poor mood symptoms in adults with MS is approximately three times that of the general population. 34 This emphasizes the importance of engaging in moderate-intensity exercise for people with MS to potentially manage and perhaps prevent this cluster of negative mood symptoms. The ability of these exercise stimuli to induce positive effects less than 5 minutes after the termination of exercise suggests that exercise is particularly useful when dealing with acute mood sympfor fatigue (F 1,23 = 2.54, η p 2 = 0.10).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Interferon beta therapy, a commonly used immunomodulatory treatment, has been implicated to cause depression in individuals with MS 22 ; however, there have also been reports indicating no association between IFNβ therapy and depression. 23 In reviewing the medication history of the 45 people with depression in the present study, 25 patients (56%) were not taking IFNβ medication, 10 (22%) had depression, and the remaining 10 (22%) were depressed regardless of immunomodulatory therapy. Therefore, most (35 of 45 [78%]) of the depressed patients in the MS cohort had depression that was unassociated specifically with IFNβ medication, lending support to previous studies 23 showing no association between depression and IFNβ medication.…”
Section: Discussionmentioning
confidence: 82%
“…23 In reviewing the medication history of the 45 people with depression in the present study, 25 patients (56%) were not taking IFNβ medication, 10 (22%) had depression, and the remaining 10 (22%) were depressed regardless of immunomodulatory therapy. Therefore, most (35 of 45 [78%]) of the depressed patients in the MS cohort had depression that was unassociated specifically with IFNβ medication, lending support to previous studies 23 showing no association between depression and IFNβ medication. With some evidence indicating that an increasing number of patients are choosing to change from IFNβ to oral medi- PRACTICE POINTS…”
Section: Discussionmentioning
confidence: 82%